A new theory of absence experience. (2nd August 2020) - Gow, Laura
Abstract: Ordering your morning coffee and then realising that your wallet is missing from your bag triggers an experience of the absence of your wallet. Familiar cases like this one provide good evidence for the idea that we frequently experience absences. According to one popular view, we experience absences by perceiving them. I argue that there are a number of problems with the perceptual view, and propose an alternative, cognitive account. Now, a cognitive account of absence experience has already been widely discussed and unequivocally rejected by participants in the debate. However, arguments against it depend upon the important, yet mistaken assumption that cognitive accounts must appeal to beliefs or judgements. I argue that the phenomenology involved in absence experience is not that associated with belief or judgement, but is instead an intellectual seeming. This renders my account immune to the objections that have been made against the existing cognitive view.